Determinants of Walking among Middle-Aged and Older Overweight and Obese Adults: Sociodemographic, Health, and Built Environmental Factors - Samuel N. Forjuoh; Marcia G. Ory; Jaewoong Won; Samuel D. Towne; Suojin Wang; Chanam Lee (Journal of Obesity)
Background. This study examined the association between selected sociodemographic, health, and built environmental factors and walking behaviors of middle-aged and older overweight/obese adults. Methods. Subjective data were obtained from surveys administered to community-dwelling overweight/obese adults aged ≥50 years residing in four Texas cities from October 2013 to June 2014, along with objective data on neighborhood walkability (Walk Score™). Multivariate logistic regression identified factors predicting the odds of walking the recommended ≥150 minutes per week for any purpose. Results. Of 253 participants, the majority were non-Hispanic white (81.8%), married (74.5%), and male (53.4%) and reported an annual income of ≥$50,000 (65.5%). Approximately, half were employed (49.6%) or had at least a college degree (51.6%). Walking the recommended ≥150 minutes per week for any purpose (n=57, 22.5%) was significantly associated with having at least a college degree (OR=5.55, 95% CI = 1.79–17.25), having no difficulty walking a quarter of a mile (OR=5.18, 95% CI = 1.30–20.83), and being unemployed (OR=3.25, 95% CI = 1.18–8.93) as well as perceived presence of sidewalks/protected walkways (OR=3.56, 95% CI = 1.10–11.50) and perceived absence of distracted drivers in the neighborhood (OR=4.08, 95% CI = 1.47–11.36). Conclusion. Addressing neighborhood conditions related to distracted drivers and pedestrian infrastructure may promote walking among middle-aged and older overweight/obese individuals.